An estimation of displacement limits for ductile systems. - Paulay, Tom (Earthquake engineering & structural dynamics.)
To enable acceptable seismic displacement demands to be specified, the displacement capacity of a structural system needs to be known. This is controlled by selected performance criteria. It is postulated that the assignment of fractions of the required strength of the system to its components may be arbitrary. This then enables the displacement capacity of buildings to be evaluated without the knowledge of its seismic strength. A redefinition of some traditionally used structural properties is a prerequisite to applications. The study of a reinforced concrete wall frame dual system illustrates rationale and extreme simplificity of application.